A força normativa da boa-fé objetiva - Hora Neto, João (2021)
Despite gestating in Roman contractualism (bona fides), this thesis asks whether objective good faith has an expansionist vocation/normative force capable of reaching other branches of private law and, also, public law, as well as whether it has a nature principle, properly applied in the light of constitutional civil legality. The general objective is to investigate whether there is an expansionist vocation, as well as whether objective good faith is a norm-rule or a principlenorm and whether its practical application is in accordance with the premises of constitutional civil law. The methodology used was documentary/bibliographic research, national and foreign, with data collection through bibliographic material, through doctrinal, jurisprudential and legal texts investigation, in addition to a dogmatic approach, by logical, grammatical and systematic interpretation, in accordance with the deductive, inductive and dialectical reasoning. According to the eight chapters exposed, it became evident that the constitutionalization of civil law requires a re-reading in the light of its strict premises, given the imprecise application of several general clauses and, among them, objective good faith. The express acceptance of objective good faith in the Civil Code was noted, visible for its triple function, as well as its connection with the contract since Roman law, and, in modernity, its close connection with its modern conception, was noted, with a constitutionalized profile, through civil, business and consumer contracts. It was observed that objective good faith is a rule of public order (loyalty/conduct/honesty) that imposes 'duties of consideration/conduct' arising from the modern conception of obligation (dynamic, cooperative, solidary) and that are independent the will of the contracting parties and are not bound by a particular type of contract. Its incidence was also observed in any contractual phase (pre, during and post), including in other branches of private law. In view of the overcoming of the summa divisio and considering that the Brazilian legal system adopts an open normative model, permeated by general clauses, the incidence of objective good faith was also demonstrated in terms of public law, as it is an ethical-legal principle and a transdisciplinary legal category, whose aim is to achieve the maximum realization of a constitutional value. The transformation of civil liability in postmodern society ('risk society') was examined in view of the mitigation of its classic assumptions (guilt, nexus and damage) and a fourth evolutionary phase of state civil liability was pointed out, that is, the State as guarantor of fundamental rights, which is why the specific state omission must be recognized in the light of new principles, and, among which, objective good faith. It was attested that such specific omission constitutes an infringement of the duty of diligence of the Constitutional State, thus violating the 'duties of consideration' relating to objective good faith, which is also rooted in constitutional principle (morality, efficiency, security, legality etc.). It was argued that objective good faith is a principle-norm (optimization command) and not a norm-rule, being subject to restriction, through the proportionality test, the result of which generates its essential content, thus present in the private law and public law. It was noted that the Brazilian legal system does not follow the Free Law School, which rejects the culture of judicial decisionism in force. Finally, it was concluded that objective good faith, regardless of Roman contractual law, has a normative force to reach the other branches of law (private and public), being a principle-norm that generates an essential content and that, in view of of its imprecise practical application, it must be operationalized in the light of constitutional civil legality, regarding legal certainty, based on the authority of the argument and not on the argument of authority (arbitrary, sentimental and ideological).